Modern trends in identification of causative agents in infective endocarditis - E. O. Kotova; E. A. Domonova; Zh. D. Kobalava; J. L. Karaulova; A. S. Pisaryuk; A. V. Balatskiy; V. G. Akimkin (Столичная издательская компания, 2021)
Advances in the diagnosis and treatment of patients with infectious endocarditis are limited by the high frequency of cases with an unknown etiology and imperfection of microbiological (cultural) methods. To overcome these problems new approaches to the identification of infectious endocarditis pathogens were introduced, which allowed achieving certain positive results. However, it should be noted that despite the wide variety of diagnostic tools currently used, there is no ideal method for etiological laboratory diagnosis of infectious endocarditis. The article discusses the features and place of immunochemical, molecular biological (MALDI-TOF MS, real-time PCR, sequencing, in situ fluorescence hybridization, metagenomic methods, etc.), immunohistochemical methods, and their advantages and limitations.